The Effect of Acupuncture Therapy and Murraya paniculata (Jiǔ Lǐ Xiāng) Infusion on Reducing Body Mass Index (BMI) in Patients with Stomach-Heat Syndrome Obesity - Dedeh Nurhasanah; Aryaprana Nando; Muslihatin Khuril R; Anis Lupita Ningrum; Franciscus Xaverius (Green Publisher Indonesia, 2025)
Background: Obesity (Féi Pàng) is one of the health problems that has increased significantly in Indonesia. Based on Riskesdas 2023, the national obesity prevalence reaches 28.7% and is higher in the group of women of childbearing age. Obesity contributes to metabolic disorders, the risk of non-communicable diseases, as well as hormonal and reproductive dysfunction. In Traditional Chinese Medicine (PTT), obesity is seen as a result of imbalances in spleen and stomach function, moisture accumulation, and gastric heat syndrome (Wei Re). Proper treatment requires holistic approaches such as acupuncture and herbs. One of the herbs used is Murraya paniculata (Jiǔ lǐ xiāng), which empirically and pharmacologically has hypolipidemic and heat-decay effects. This therapy is believed to reduce Body Mass Index (BMI) effectively. Objective: This study aimed to determine the effect of acupuncture therapy and Murraya paniculata (Jiǔ lǐ xiāng) on the reduction of BMI in obese women with gastric heat syndrome. Methods: The study used a pre-experimental quantitative design with a one group pretest-posttest design. The sample consisted of 20 women aged 21–36 years who underwent therapy 6 times for 2 weeks at the Petos Sehat Clinic in Jakarta. Data were collected through BMI measurements before and after the intervention. The sampling technique uses purposive sampling. The data was analyzed using a paired t-test statistical test. Results: The average BMI before therapy showed a value of 30.19 kg/m² After the intervention, the average BMI decreased to 29.31 kg/m².